THE EFFECT OF PROFITABILITY AND LIQUIDITY RATIO ON COMPANY STOCK PRICES IN THE PROPERTY SECTOR - Rafida Khairani; Fati Syafira; Masnika Sinaga; Roryn Chelsi Gea; Lorensisca Sitorus (Jurnal Ilmu Manajemen Profitability, 2021)
The purpose of this research is to analyze the effect of profitability and Liqudity on the company's stock price in Property Sector. This research uses a quantitative approach, the type of research used is associative research. The data used are secondary data in the form of company financial statements obtained from the Indonesia Stock Exchange (IDX). In determining the sample of this study using a purposive sampling method that is determining the sample by making certain criteria. The data analysis method uses multiple linear regression analysis. Testing the hypothesis in this study using the t test to determine the effect of individual independent variables on the dependent variable. While the F test is used to determine the effect of Current Ratio (CR), Net Profit Margin (NPM), Return On Assets (ROA) simultaneously on stock prices. The regresion results of this research shows that independent variables like CR and ROA has a positive effect in predicting stock prices. While, the NPM variable has a negative effect in predicting the stock prices. Current Ratio (CR), Net Profit Margin (NPM), and Return On Assets (ROA) simultaneously have a significant effect on Stock Prices. Partially, Current Ratio (CR), and Return On Assets (ROA) have a significant effect on Stock Prices. While Net Profit Margin (NPM) Does not have significant effect on Stock Prices. From the regression coefficient test concluded that 58,8% of the share price can be explained by the independent variables